A scoping review of qualitative studies on sexual and reproductive health and rights in Uganda: Exploring factors at multiple levels - Buser, Julie M; Kumakech, Edward; August, Ella; Rana, Gurpreet K; Gray, Rachel; Auma, Anna Grace; Jacobson-Davies, Faelan E; Endale, Tamrat; Pebolo, Pebalo Francis; Smith, Yolanda R (Women's health (London, England), 2024)
Background: Uganda is burdened by high unintended and teen pregnancies, high sexually transmitted infections, and harm caused by unsafe abortion. Objectives: Explore factors influencing sexual and reproductive health and rights (SRHR) in Uganda by synthesizing evidence from qualitative studies using a scoping review. Eligibility Criteria: Original qualitative peer-reviewed research studies published between 2002 and 2023 in any language exploring factors influencing SRHR in Uganda. Sources of Evidence: Eight databases searched using qualitative/mixed methods search filters and no language limits. Charting Methods: Information extracted included author, article title, publication year, study aims, participant description, data collection type, sample size, main findings, factors at the individual, interpersonal, community, and policy levels, implications for SRHR in Uganda, and study limitations. Quality of the selected articles was assessed using the Critical Appraisal Skills Programme tool. Results: One hundred seventy-three studies met inclusion criteria. At the individual level, knowledge and attitudes toward SRHR, risky sexual behavior, and access to maternal SRHR services were identified as critical factors influencing health outcomes. Interpersonal factors included communication with sexual partners and relationships with family, school, and community members. Healthcare organization factors included adolescent access to education, SRHR services, and HIV prevention. Cultural and social factors included gendered norms and male involvement in SRHR. Policy-level factors included the importance of aligning policy and practice. Conclusions: Multiple factors at individual, interpersonal, community, healthcare, cultural, and policy levels were found to influence SRHR in Uganda. The findings suggest that interventions targeting multiple levels of the socio-ecological system may be necessary to improve SRHR outcomes. This review highlights the need for a holistic approach that considers the broader socio-ecological context. Reducing identified gaps in the literature, particularly between policy and practice related to SRHR, is urgently needed in Uganda. We hope this review will inform the development of policies and interventions to improve SRHR outcomes. Plain language summary A scoping review of qualitative studies on sexual and reproductive health and rights in Uganda In Uganda, there are significant challenges regarding sexual and reproductive health and rights (SRHR), including high rates of unintended and teen pregnancies, sexually transmitted infections, and unsafe abortions. To better understand these issues, we conducted a comprehensive review of qualitative studies published between 2002 and 2023. Our analysis identified 173 studies that revealed various factors influencing SRHR in Uganda across different levels. At the individual level, factors such as knowledge and attitudes toward SRHR, risky sexual behavior, and access to maternal SRHR services were found to significantly impact health outcomes. Interpersonal relationships also played a crucial role, with communication with sexual partners and relationships with family, school, and community members being identified as important influences. Furthermore, the organization of healthcare services was found to be vital, particularly regarding adolescent access to education, SRHR services, and HIV prevention. Cultural and social factors, including gender norms and the involvement of males in SRHR, were noted as significant contributors to SRHR outcomes. Additionally, the alignment of policy and practice was emphasized as essential for improving SRHR outcomes in Uganda. Overall, the review concluded that addressing SRHR challenges in Uganda requires interventions that target multiple levels of the socio-ecological system. A holistic approach considering individual, interpersonal, community, healthcare, cultural, and policy factors is necessary. There is an urgent need to bridge gaps between policy and practice related to SRHR. Findings could inform the development of policies and interventions aimed at improving SRHR outcomes in Uganda.